جريمة الاحتيال بالسحر والشعوذة - الشمري، راسم مسير جاسم (كلية المنصور الجامعة, 2016)
كان لموضوع جريمة الاحتيال بالسحر والشعوذة أهمية في الحياة بشكل عام وليس حصراً على الواقع القانوني، ونظراً لأتساع ممارسة السحر والشعوذة في المجتمع، ولخلو التشريع العراقي من نص صريح يجرم أفعال الذين يقومون بأعمال السحر للحصول على المال. لأتساع هذا النوع ونموه متخذين أسماء وعناوين مختلفة فمنهم من يسمى نفسه (العراف) أو (المنجم) أو (الساحر) أو (قارئ الطالع) فقد بثت بين أوساط الناس سواء منهم المتعلم والجاهل الخراب والدمار فأصابت الفرد والمجتمع بل حتى وصلت آثارها إلى الحكام والملوك والرؤساء فأخذوا يتدخلون في مصير البلاد والعباد بطريق السحر، هذا بالإضافة إلى أن الكثير من فقدوا راحة القلب وطمأنينة النفس بلجؤهم إلى السحرة والمشعوذين لحل مشاكلهم فكانوا كالمستجير من الرمضاء بالنار. وكان اختلاف الفقهاء والمشرعين بنظرتهم لهذه الأفعال فمنهم من وصفها كونها من جرائم التشرد والآخر اعتبرها جريمة خاصة بينما عدها آخرون جريمة احتيال وعدت من غيرهم آحتيال ونصب هذه الأمور تشكل صعوبة في التكييف والتنظيم والرقابة لذلك يتطلب الأمر معالجتها تشريعياً. لذا فقد قسمنا هذا الموضوع الى مبحثين:- تناولنا في المبحث الأول التطور التاريخي والتشريعي لجريمة الاحتيال بالسحر ومبحث ثانى اركان جريمة الاحتيال بالسحر وخصائصها وانواعها.
The crime of fraud through witchcraft and sorcery has been quite important not only in the legal area but also in life, in general. Because the practice of witchcraft and sorcery in the community has increased and because there is no clear article in the Iraqi legislation condemning these acts which are done for the sake of getting money, this state has terribly affected both the individual and the community (including rulers, kings and presidents).many have lost their peace of mind as a result of listening to these tricky persons. In reality, people have embarked on these practices to solve their problems and to get some comfort but that has deplorably made them more miserable. Those practicing this kind of crime have different names such as fortune- tellers, astrologers, magicians and horoscope reader. Jurists and legislators differ in looking at these evil acts. Some have described them as special crimes. Still others have considered them as crimes of fraud. These things constitute, in fact, some difficulty concerning regulations, censorship and adoption, a thing which has required that these practices should be treated through legislations. The researcher, accordingly, has discussed tow topics in the paper. The first topic surveys the historical and legal development of the crime of fraud by witchcraft and sorcery. The second one deals with the basic elements of the crime of fraud by witchcraft, suggesting its characteristics. The research ends by providing a conclusion.
Keywords: الجريمة والمجرمون -- الدجل والشعوذة -- النصب والإحتيال -- السحر -- القوانين والتشريعات -- الأحكام القضائية -- مستخلصات الأبحاث